The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/2030818
|View full text |Cite
|
Sign up to set email alerts
|

Wheel-Running Exercise Protects Ovariectomized Mice from Bone Loss via IFN-γ-Mediated Suppression of the NF-κB and MAPK Pathways

Abstract: Physical exercise is recommended as a preventative approach for osteoporosis; however, the effect of physical exercise on bone mass remains controversial. Additionally, the immune regulation of physical exercise on bone mass remains unclear. To determine whether wheel-running (WR) exercise contributes to improving bone mineral density (BMD) and investigate the involved immune mechanism, ovariectomized (OVX) and sham-operated mice were treated with 8 weeks of WR exercise. The distal femurs of the mice were sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In an IFN-γ-mediated immunomodulatory approach, Hao Shen et al. demonstrated that WR exercise prevented bone loss in OVX mice ( 209 ). Activated CD8 T lymphocytes restored IFN-γ expression after WR exercise, which prevented OC formation and restored bone loss via NF-κB and MAPK pathways.…”
Section: Ifn-γ In the Treatment Of Osteoporosismentioning
confidence: 99%
“…In an IFN-γ-mediated immunomodulatory approach, Hao Shen et al. demonstrated that WR exercise prevented bone loss in OVX mice ( 209 ). Activated CD8 T lymphocytes restored IFN-γ expression after WR exercise, which prevented OC formation and restored bone loss via NF-κB and MAPK pathways.…”
Section: Ifn-γ In the Treatment Of Osteoporosismentioning
confidence: 99%
“…In addition, the LRP family proteins and Wnt/β-catenin pathway are regulated by exercise, which improves bone remodeling, bone mass recovery, and bone stiffness in rats with disuse osteoporosis (Chen et al, 2016;Jia et al, 2019). Roller exercises prevent osteoporosis by activating CD8 T cells to release IFN-γ, which exhibits the effects of inhibiting osteoclast formation and recovering bone loss through NF-κB and MAPK pathways (Shen et al, 2022) (Figure 1).…”
Section: The Mechanism Of Chinese Traditional Fitness Exercises In Im...mentioning
confidence: 99%
“…By measuring and comparing the BMD of postmenopausal athletes with different levels of physical activity, Yang et al concluded that long-term exercise effectively prevented bone loss in female athletes and improved their musculoskeletal fitness (87). In addition, wheelrunning exercise prevented bone loss in OVX mice (56). RNAsequencing technology in the peripheral blood mononuclear cells (PBMCs) of OVX rats was also used to investigate the effect of moderate-intensity treadmill exercise on the sensitive genes related to bone mass (88).…”
Section: Postmenopausal Osteoporosismentioning
confidence: 99%
“…The majority of proinflammatory cytokines such as IL-6, TNF-α, IL-1, and IFN-γ play a pivotal role in the treatment of osteoporosis through exercise ( 54 56 ). Exercise may improve inflammation by upregulating anti-inflammatory factors, which may have an effect on bone metabolism ( 57 ).…”
Section: Mechanisms Of Exercise On Bone Healthmentioning
confidence: 99%
See 1 more Smart Citation